Optical adhesive with low modulus, high creep and high peel strength, preparation method thereof and optical bonding sheet
By reducing the use of polar monomers and designing a low-modulus OCA optical glue and tackifier compound, the fatigue problem caused by high modulus in folding screens is solved, and high peel strength and good creep are achieved. The reply effect meets the bending resistance performance requirements of the foldable screen.
Patent Information
- Application Number
- CN202411530385.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
In foldable screen applications, traditional OCA optical pressure-sensitive adhesives are fatigued due to high modulus and strong bonding performance, resulting in bonding failure, which cannot meet the bending resistance of foldable screen phones.
By reducing the use of polar monomer acrylic acid, a low-modulus OCA optical glue is designed, and copolymerized with acrylic-2-ethyl acrylic acid to form a small molecule tackifier additive, combined with OCA optical glue to improve peel strength.
The optical adhesive with low modulus, high creep, high peel strength is achieved, which avoids the problem of sudden increase in energy storage modulus, maintains good creep recovery effect and high peeling force, and satisfies the folding screen at high and low temperatures. Use requirements.
Smart Images

Figure BDA0005110335480000111 
Figure BDA0005110335480000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical adhesive materials, and in particular to an optical adhesive with low modulus, high creep and high peel strength, a preparation method thereof and an optical adhesive sheet. Background Art
[0002] With the rapid development of modern electronic information, traditional displays can no longer meet people's daily needs. Curved displays, curved screens, foldable screens and wearable devices are entering the public's field of vision, and people are increasingly interested in flexible displays. The emergence of these new displays has put forward new requirements for the performance of OCA optical pressure-sensitive adhesives. The replacement of folding screens has also put forward higher requirements for the bending resistance, modulus, creep and peel strength of OCA adhesives. Traditional OCA has the characteristics of high modulus and strong bonding performance. The stress generated during the folding process will cause serious material fatigue of the material, causing it to fail in actual application, thereby greatly reducing the user experience and service life of folding screen mobile phones. At present, the OCA optical pressure-sensitive adhesive used in foldable screen mobile phones is required to have three properties: (1) low storage modulus, which can produce high shear strain and only produce small stress under high deformation; (2) high resilience, which can quickly recover under long-term static folding; (3) high interfacial adhesion to prevent delamination and separation of adhesives under stress.
[0003] At present, traditional OCA glue increases the usage of polar monomers such as hydroxyl-containing monomers and carboxyl-containing monomers in order to improve the peel strength. However, the usage of these polar monomers significantly increases the modulus of the OCA glue, making the glue hard and even gelling, which is not conducive to the bending resistance of the screen in actual use. Summary of the invention
[0004] In view of the above problems, the present invention proposes a solution, namely, reducing the usage of polar monomers such as acrylic acid in the main adhesive formula, designing and synthesizing an OCA optical adhesive polymer with a low modulus, and copolymerizing a large amount of acrylic acid with 2-ethyl acrylate to design and synthesize a small molecule viscosity-enhancing agent. By compounding the viscosity-enhancing agent with the OCA optical adhesive, the peel strength can be greatly improved while ensuring the low modulus and high creep effect of the main adhesive.
[0005] To achieve the above-mentioned object, the technical solution adopted by the present invention is: In the first aspect of the present invention, a low modulus, high creep and high peel strength optical adhesive is provided, characterized in that it comprises the following raw material components in parts by weight: 100 parts of OCA optical adhesive, 4-7 parts of tackifier, 0.01-0.03 parts of curing agent and 0.04-0.07 parts of organic tin catalyst;
[0006] The raw materials for preparing the OCA optical adhesive include, by weight: 26-31 parts of a first soft monomer, 1-2 parts of a hard monomer, 1-3 parts of a first functional monomer, 0.03-0.1 parts of a first initiator, and 65-70 parts of a first solvent. The molecular weight of the OCA optical adhesive is 1.2 million to 1.6 million, and the rotational viscosity is 1000-2000 mpa*s.
[0007] Preferably, the OCA optical adhesive is prepared by the following method:
[0008] The first soft monomer, the hard monomer and the first functional monomer are added to part of the first solvent, nitrogen is introduced at 60-63°C for 30 minutes, and then the first part of the first initiator is added, and the reaction is continued for 3 hours. The second part of the first initiator is added and the reaction is continued for 3 hours. Then, the temperature is raised to 65-67°C and the remaining third part of the first initiator is added, and the reaction is continued for 3 hours. After the reaction is completed, the temperature is lowered, and the remaining part of the first solvent is added for dilution to obtain the OCA optical adhesive.
[0009] Preferably, the first soft monomer is one or more of ethyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, octadecyl acrylate, and ethoxyethyl acrylate;
[0010] The hard monomer is one or more of methyl methacrylate, ethyl methacrylate, acrylonitrile, acryloylmorpholine, and N-vinyl pyrrolidone;
[0011] The first functional monomer is one or more of 2-hydroxyethyl acrylate, 2-hydroxybutyl acrylate, acrylamide, acrylic acid, and glycidyl acrylate.
[0012] Preferably, the raw materials for preparing the tackifier include, by weight: 25-28 parts of a second soft monomer, 2-4 parts of a second functional monomer, 0.5-1.5 parts of n-dodecyl mercaptan, 0.4-0.7 parts of a second initiator, and 65-70 parts of a second solvent; the tackifier has a molecular weight of 12000-16000 and a rotational viscosity of 100-500 mpa*s.
[0013] Preferably, the second soft monomer is at least one of butyl acrylate and 2-ethyl acrylate;
[0014] The second functional monomer is at least one of acrylic acid, hydroxyethyl acrylate and hydroxybutyl acrylate.
[0015] Preferably, the tackifying aid is prepared by the following method:
[0016] The second soft monomer, the second functional monomer and n-dodecyl mercaptan are added to the second solvent, nitrogen is introduced at 65-70° C. for 30 minutes, and then the second initiator is added and reacted for 7 hours to obtain the viscosity-enhancing agent.
[0017] Preferably, the first initiator and the second initiator are one or more of azobisisobutyronitrile, azobisisoheptylnitrile, or both of dibenzoyl peroxide;
[0018] The first solvent and the second solvent are both ethyl acetate.
[0019] Preferably, the curing agent is one or more of hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, and aluminum acetylacetonate;
[0020] The organic tin catalyst is one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate.
[0021] The second aspect of the present invention provides a method for preparing the optical adhesive with low modulus, high creep and high peel strength as described above, the method comprising: mixing OCA optical glue, curing agent, tackifier and organic tin catalyst, stirring for 5-20 minutes at a temperature of 20-35°C, evacuating, and standing until there are no bubbles to obtain the optical adhesive with low modulus, high creep and high peel strength.
[0022] In a third aspect of the present invention, there is provided an optical adhesive sheet with low modulus, high creep and high peel strength, which is prepared by the following method:
[0023] The optical adhesive with low modulus, high creep and high peel strength as described in any one of claims 1 to 8 is uniformly coated on a release film, baked at 110-130° C. for 1-5 min, covered with another layer of release film on the adhesive surface, and then aged in an oven at 50-60° C. for 24-72 h to obtain the optical adhesive sheet with low modulus, high creep and high peel strength.
[0024] The beneficial effects of the present invention are:
[0025] The present invention provides an optical adhesive with low modulus, high creep and high peel strength, a preparation method thereof and an optical adhesive sheet based on the optical adhesive. The present invention uses a low molecular weight polymer formed by copolymerizing a large amount of acrylic acid and 2-EHA as a tackifying resin to increase the peeling force, thereby avoiding the adverse consequence of a sudden increase in the storage modulus caused by the use of a large amount of polar monomers in OCA optical adhesives, so that the storage modulus and Tg of the entire system are maintained at a low level while having a high peeling force and good.
[0026] The optical adhesive sheet prepared by the present invention has a high peeling force while maintaining a low storage modulus and a good creep recovery effect, and has good folding performance at both high and low temperatures, can meet use requirements, and has a good market application prospect. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0028] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0029] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0030] The present invention provides an optical adhesive with low modulus, high creep and high peel strength, comprising the following raw material components by weight: 100 parts of OCA optical adhesive, 4-7 parts of tackifier, 0.01-0.03 parts of curing agent and 0.04-0.07 parts of organic tin catalyst;
[0031] In a preferred embodiment, the raw materials for preparing OCA optical adhesive include, by weight: 26-31 parts of a first soft monomer, 1-2 parts of a hard monomer, 1-3 parts of a first functional monomer, 0.03-0.1 parts of a first initiator, 65-70 parts of a first solvent, the molecular weight of the OCA optical adhesive is 1.2 million to 1.6 million, and the rotational viscosity is 1000-2000 mPa*s; the OCA optical adhesive within this range has good modulus and creep effect, and does not require further dilution during coating.
[0032] In a preferred embodiment, the OCA optical adhesive is prepared by the following method:
[0033] The first soft monomer, the hard monomer and the first functional monomer are added to part of the first solvent, nitrogen is introduced at 60-63°C for 30 minutes, and then the first part of the first initiator is added, and the reaction is continued for 3 hours. The second part of the first initiator is added and the reaction is continued for 3 hours. Then, the temperature is raised to 65-67°C and the remaining third part of the first initiator is added, and the reaction is continued for 3 hours. After the reaction is completed, the temperature is lowered, and the remaining part of the first solvent is added to dilute to obtain OCA optical adhesive.
[0034] In a preferred embodiment, the first soft monomer is one or more of ethyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, octadecyl acrylate, and ethoxyethyl acrylate.
[0035] In a preferred embodiment, the hard monomer is one or more of methyl methacrylate, ethyl methacrylate, acrylonitrile, acryloylmorpholine, and N-vinyl pyrrolidone.
[0036] In a preferred embodiment, the first functional monomer is one or more of 2-hydroxyethyl acrylate, 2-hydroxybutyl acrylate, acrylamide, acrylic acid, and glycidyl acrylate.
[0037] In a preferred embodiment, the raw materials for preparing the tackifier include, by weight: 25-28 parts of a second soft monomer, 2-4 parts of a second functional monomer, 0.5-1.5 parts of n-dodecyl mercaptan, 0.4-0.7 parts of a second initiator, and 65-70 parts of a second solvent; the molecular weight of the tackifier is 12000-16000, and the rotational viscosity is 100-500mpa*s; the tackifier within this range not only has little effect on the modulus and creep of the main adhesive, but also can greatly improve the peel strength.
[0038] In a preferred embodiment, the second soft monomer is at least one of butyl acrylate and 2-ethyl acrylate.
[0039] In a preferred embodiment, the second functional monomer is at least one of acrylic acid, hydroxyethyl acrylate and hydroxybutyl acrylate.
[0040] In a preferred embodiment, the tackifying aid is prepared by the following method:
[0041] The second soft monomer, the second functional monomer and n-dodecyl mercaptan are added to the second solvent, nitrogen is introduced at 65-70° C. for 30 minutes, and then the second initiator is added and reacted for 7 hours to obtain a viscosity-enhancing agent.
[0042] In a preferred embodiment, the first initiator and the second initiator are both one or more of azobisisobutyronitrile, azobisisoheptanenitrile, or both of dibenzoyl peroxide.
[0043] In a preferred embodiment, the first solvent and the second solvent are both ethyl acetate.
[0044] In a preferred embodiment, the curing agent is one or more of hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, and aluminum acetylacetonate.
[0045] In a preferred embodiment, the organotin catalyst is one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate, more preferably dibutyltin dilaurate.
[0046] The present invention also provides a method for preparing the optical adhesive with low modulus, high creep and high peel strength as above, which comprises: mixing OCA optical adhesive, curing agent, tackifier and organic tin catalyst, stirring for 5-20 minutes at a temperature of 20-35°C, evacuating, and standing until there are no bubbles, to obtain the optical adhesive with low modulus, high creep and high peel strength.
[0047] The present invention also provides an optical adhesive sheet with low modulus, high creep and high peel strength, which is prepared by the following method:
[0048] The optical adhesive with low modulus, high creep and high peel strength as above is evenly coated on the release film, baked at 110-130°C for 1-5 minutes, covered with another layer of release film on the adhesive surface, and then aged in an oven at 50-60°C for 24-72 hours to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0049] The above is the general concept of the present invention, and detailed examples and comparative examples are provided below on the basis of the above to further illustrate the present invention. The raw material parts involved below are all parts by weight.
[0050] Example 1
[0051] S1. Preparation of OCA optical adhesive
[0052] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then heat to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0053] S2. Preparation of viscosity enhancing agent
[0054] Accurately weigh 67 parts of ethyl acetate, 26 parts of 2-ethyl acrylate, 2 parts of acrylic acid, and 1 part of n-dodecyl mercaptan, mix well, and place in a four-necked flask equipped with a stirrer, a condenser, and a nitrogen tube. Pass nitrogen gas and stir at 65° C. for at least 30 minutes; add 0.7 parts of initiator AIBN and react at 68° C. for 7 hours to obtain a viscosity-enhancing agent.
[0055] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0056] S3-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate, 0.005 parts of aluminum acetylacetonate curing agent, 4 parts of adhesion promoter, and 0.03 parts of dibutyltin dilaurate in sequence, mix and stir at 25°C for 10 minutes, evacuate the mixture, and let it stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0057] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0058] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0059] Example 2
[0060] S1. Preparation of OCA optical adhesive
[0061] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0062] S2. Preparation of viscosity enhancing agent
[0063] Accurately weigh 67 parts of ethyl acetate, 25 parts of 2-ethyl acrylate, 3 parts of acrylic acid, and 1 part of n-dodecyl mercaptan, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 65°C for 30 minutes; add 0.7 parts of initiator AIBN and react at 68°C for 7 hours to obtain a viscosity-enhancing agent.
[0064] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0065] S3-1. Weigh 100 grams of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, 6 parts of adhesion promoter, and 0.03 parts of dibutyltin dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate, and let stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0066] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0067] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0068] Example 3
[0069] S1. Preparation of OCA optical adhesive
[0070] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0071] S2. Preparation of viscosity enhancing agent
[0072] Accurately weigh 67 parts of ethyl acetate, 26 parts of 2-ethyl acrylate, 2 parts of acrylic acid, and 1 part of n-dodecyl mercaptan, mix well, and place in a four-necked flask equipped with a stirrer, a condenser, and a nitrogen tube. Pass nitrogen gas and stir at 65°C for 30 minutes; add 0.7 parts of initiator AIBN and react at 68°C for 7 hours to obtain a viscosity-enhancing agent.
[0073] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0074] S3-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, 6 parts of adhesion promoter, 0.03 parts of dibutyltin dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate, and let stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep and high peel strength.
[0075] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0076] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0077] Comparative Example 1
[0078] S1. Preparation of OCA optical adhesive
[0079] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0080] S2. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0081] S2-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, and 0.03 parts of dibutyltin dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate the mixture, and let it stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0082] S2-2. Apply 50 μm thick optical adhesive on the release surface of T2 release film, bake at 120°C for 3 min, and then attach T4 release film on its surface.
[0083] S2-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0084] Comparative Example 2
[0085] S1. Preparation of OCA optical adhesive
[0086] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0087] S2. Preparation of viscosity enhancing agent
[0088] Accurately weigh 67 parts of ethyl acetate, 26 parts of 2-ethyl acrylate, 1 part of acrylic acid, and 1 part of n-dodecyl mercaptan, mix them evenly, place them in a four-necked flask equipped with a stirrer, a condenser, and a nitrogen tube, introduce nitrogen, and stir at 65°C for 30 minutes; then add 0.7 parts of initiator AIBN and react at 68°C for 7 hours to obtain a tackifier.
[0089] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0090] S3-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, 6 parts of adhesion promoter, and 0.03 parts of dibutyltin dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate the mixture, and let it stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0091] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0092] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0093] Comparative Example 3
[0094] S1. Preparation of OCA optical adhesive
[0095] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0096] S2. Preparation of viscosity enhancing agent
[0097] Accurately weigh 67 parts of ethyl acetate, 24 parts of 2-ethyl acrylate, 6 parts of acrylic acid, and 1 part of n-dodecyl mercaptan, mix well, and place in a four-necked flask equipped with a stirrer, a condenser, and a nitrogen tube. Pass nitrogen gas and stir at 65°C for 30 minutes; add 0.7 parts of initiator AIBN and react at 68°C for 7 hours to obtain a viscosity-enhancing agent.
[0098] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0099] S3-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, 6 parts of adhesion promoter, and 0.03 parts of dibutyl dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate the mixture, and let it stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0100] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0101] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0102] Comparative Example 4
[0103] S1. Preparation of OCA optical adhesive
[0104] Accurately weigh 50 parts of ethyl acetate, 14 parts of 2-ethyl ethyl acrylate, 15 parts of ethoxyethoxyethyl acrylate, 2 parts of acryloylmorpholine, 1.5 parts of hydroxybutyl acrylate, and 0.1 part of acrylic acid, mix well and place in a four-necked flask equipped with a stirrer, a condenser and a nitrogen tube, introduce nitrogen, and stir at 60°C for at least 30 minutes; add 0.04 parts of initiator AIBN and react at 62°C for 3 hours, then add 0.04 parts of initiator to react for 3 hours; then raise the temperature to 67°C and continue to add 0.06 parts of initiator to react for 3 hours; after cooling, add 17 parts of ethyl acetate to dilute to obtain OCA optical adhesive.
[0105] S2. Preparation of viscosity enhancing agent
[0106] Accurately weigh 67 parts of ethyl acetate, 24 parts of 2-ethyl acrylate, 5 parts of methyl methacrylate, and 1 part of n-dodecyl mercaptan, mix them evenly, place them in a four-necked flask equipped with a stirrer, a condenser, and a nitrogen tube, introduce nitrogen, and stir at 65°C for 30 minutes; then add 0.7 parts of initiator AIBN and react at 68°C for 7 hours to obtain a tackifier.
[0107] S3. Preparation of optical adhesive sheet with low modulus, high creep and high peel strength:
[0108] S3-1. Weigh 100 parts of optical adhesive A, add 0.025 parts of hexamethylene diisocyanate curing agent, 0.005 parts of aluminum acetylacetonate curing agent, 6 parts of adhesion promoter, and 0.03 parts of dibutyltin dilaurate catalyst in sequence, mix and stir at 25°C for 10 minutes, evacuate the mixture, and let it stand until there are no bubbles to obtain an optical adhesive with low modulus, high creep, and high peel strength.
[0109] S3-2. Apply 50 μm thick optical adhesive on the release surface of the T2 release film, bake at 120°C for 3 min, and then attach the T4 release film on its surface.
[0110] S3-3. Aging at 55°C for 2 days to obtain an optical adhesive sheet with low modulus, high creep and high peel strength.
[0111] The optical adhesive sheets prepared in the examples and comparative examples were subjected to the following performance tests:
[0112] 1. 180° peel strength test: Cut the test sample into 2.5cm wide strips, and the test method is carried out in accordance with the international standard ASTMD3330 "Standard for Peel Strength Test of Pressure-Sensitive Tapes". Test method: Place the test steel plate at room temperature for 20 minutes before testing, and record the average adhesion required to tear the strip off the test panel, expressed in gf / 25mm.
[0113] 2. Storage modulus test: Remove the release films on both sides of the test sample prepared above, stack multiple film layers to obtain a sample with a thickness of about 1 mm, and cut it into a disc with a diameter of 8 mm. Use a rheometer (TA Company, model: HR10) to measure the shear modulus at different temperatures. The measurement frequency is 1 Hz, and the measured storage modulus value is recorded in kPa.
[0114] The 180° peeling force, storage modulus, creep and bending resistance test data at low temperature (-20°C), room temperature (25°C) and high temperature (65°C) are shown in Table 1 below:
[0115] Table 1
[0116]
[0117]
[0118] Among them, in high-temperature dynamic bending and low-temperature dynamic bending, the OK standard is that there are no abnormal phenomena in appearance: bubbles, delamination, and severe creases.
[0119] It can be seen from the data in the table that the optical adhesive sheets prepared in Examples 1-3 have a high peel force while maintaining a low storage modulus and a good creep recovery effect, and have good folding properties at both high and low temperatures, meeting the use requirements.
[0120] By comparing Examples 1-3 with Comparative Example 1, it can be seen that the addition of the small molecule tackifier greatly improves the peel strength of the optical adhesive sheet.
[0121] By comparing Examples 1-3 and Comparative Examples 2-3, it can be seen that the content of acrylic acid in the small molecule tackifier has an important influence on the performance of the optical adhesive sheet. When the content of acrylic acid is low, the peel strength of the adhesive sheet is insufficient, and when the content of acrylic acid is high, the creep effect of the adhesive sheet as a whole is poor, and the folding performance of the optical adhesive sheet cannot be guaranteed.
[0122] In Comparative Example 4, after acrylic acid was replaced by methacrylate, the effect of increasing the peel strength was limited because the polarity of methacrylate monomer was smaller than that of acrylic acid, and the overall creep effect was also poor because it could not be cross-linked with the main glue.
[0123] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. An optical adhesive with low modulus, high creep and high peel strength, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of OCA optical adhesive, 4-7 parts of tackifier, 0.01-0.03 parts of curing agent and 0.04-0.07 parts of organic tin catalyst; The raw materials for preparing the OCA optical adhesive include, by weight: 26-31 parts of a first soft monomer, 1-2 parts of a hard monomer, 1-3 parts of a first functional monomer, 0.03-0.1 parts of a first initiator, and 65-70 parts of a first solvent. The molecular weight of the OCA optical adhesive is 1.2 million to 1.6 million, and the rotational viscosity is 1000-2000 mpa*s.
2. The optical adhesive with low modulus, high creep and high peel strength according to claim 1, characterized in that: The OCA optical adhesive is prepared by the following method: The first soft monomer, the hard monomer and the first functional monomer are added to part of the first solvent, nitrogen is introduced at 60-63°C for 30 minutes, and then the first part of the first initiator is added, and the reaction is continued for 3 hours. The second part of the first initiator is added and the reaction is continued for 3 hours. Then, the temperature is raised to 65-67°C and the remaining third part of the first initiator is added, and the reaction is continued for 3 hours. After the reaction is completed, the temperature is lowered, and the remaining part of the first solvent is added for dilution to obtain the OCA optical adhesive.
3. The optical adhesive with low modulus, high creep and high peel strength according to claim 2, characterized in that: The first soft monomer is one or more of ethyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, octadecyl acrylate, and ethoxyethyl acrylate; The hard monomer is one or more of methyl methacrylate, ethyl methacrylate, acrylonitrile, acryloylmorpholine, and N-vinyl pyrrolidone; The first functional monomer is one or more of 2-hydroxyethyl acrylate, 2-hydroxybutyl acrylate, acrylamide, acrylic acid, and glycidyl acrylate.
4. The optical adhesive with low modulus, high creep and high peel strength according to claim 1, characterized in that: The raw materials for preparing the tackifier include, by weight: 25-28 parts of a second soft monomer, 2-4 parts of a second functional monomer, 0.5-1.5 parts of n-dodecyl mercaptan, 0.4-0.7 parts of a second initiator, and 65-70 parts of a second solvent; the tackifier has a molecular weight of 12000-16000 and a rotational viscosity of 100-500 mpa*s.
5. The optical adhesive with low modulus, high creep and high peel strength according to claim 4, characterized in that: The second soft monomer is at least one of butyl acrylate and 2-ethyl acrylate; The second functional monomer is at least one of acrylic acid, hydroxyethyl acrylate and hydroxybutyl acrylate.
6. The optical adhesive with low modulus, high creep and high peel strength according to claim 5, characterized in that: The tackifying aid is prepared by the following method: The second soft monomer, the second functional monomer and n-dodecyl mercaptan are added to the second solvent, nitrogen is introduced at 65-70° C. for 30 minutes, and then the second initiator is added and reacted for 7 hours to obtain the viscosity-enhancing agent.
7. The optical adhesive with low modulus, high creep and high peel strength according to claim 6, characterized in that: The first initiator and the second initiator are one or more of azobisisobutyronitrile, azobisisoheptylnitrile, or both of dibenzoyl peroxide; The first solvent and the second solvent are both ethyl acetate.
8. The optical adhesive with low modulus, high creep and high peel strength according to claim 1, characterized in that: The curing agent is one or more of hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, and aluminum acetylacetonate; The organic tin catalyst is one or more of dibutyltin dilaurate, stannous octoate, and dibutyltin diacetate.
9. A method for preparing an optical adhesive with low modulus, high creep and high peel strength as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing OCA optical adhesive, a curing agent, a tackifier and an organic tin catalyst, stirring for 5-20 minutes at a temperature of 20-35°C, evacuating the mixture, and standing the mixture until there are no bubbles, thereby obtaining the optical adhesive with low modulus, high creep and high peel strength.
10. An optical adhesive sheet with low modulus, high creep and high peel strength, characterized in that: It is prepared by the following method: The optical adhesive with low modulus, high creep and high peel strength as described in any one of claims 1 to 8 is uniformly coated on a release film, baked at 110-130° C. for 1-5 min, covered with another layer of release film on the adhesive surface, and then aged in an oven at 50-60° C. for 24-72 h to obtain the optical adhesive sheet with low modulus, high creep and high peel strength.
Citation Information
Patent Citations
Optical adhesive with high refractive index and preparation method thereof
CN112745786A
Flexible OCA optical cement, folding mobile phone outer screen and preparation method of folding mobile phone outer screen
CN118126656A
Optically clear pressure sensitive adhesive (OCA) and preparation method therefor
WO2024007852A1